Assessing sustainable operational conditions of a bottoming organic Rankine cycle using zeotropic mixtures: An energy-emergy approach (2022)
In this work, an Organic Rankine Cycle system is used to produce electricity from the waste heat of an internal combustion engine (ICE). The toluene, and cyclohexane, are the selected pure fluids to be compared with the zeotropic mixtures. The zeotropic mixtures used as working fluids are cyclohexane/R11 (0.2/0.8), cyclohexane/R11 (0.25/0.75), and cyclohexane/R11 (0.3/0.7). An energy, exergy and emergy analysis was conducted to assess the sustainability of the whole system and the viability of the zeotropic mixture from the environmental point of view. Finally, a multi-objective optimization was carried out. The results showed that the zeotropic mixtures have better performance compared with the selected pure fluids when the net power and the exergy efficiency are considered. The pure fluids had a better Emergy Sustainability Index (ESI) index by 10% on average, there is not a big difference on this parameter so the advantages of using zeotropic mixtures as working fluids for this type of system cannot t be ignored. However, using the mixture the system obtained a lower Environmental load Ratio (ELR) value compared to cyclohexane and toluene. Finally, the multi-objective optimization was able to maximize the exergy efficiency for the working fluids by about 9.7% and reduce the ESI by 50.94%. This study intends to show the advantage and disadvantage of using zeotropic mixtures as working fluid on waste heat recovery systems that uses Organic Rankine cycle from the environmental point of view and using emergy as a way to asses the sustainability of the whole system.